Pengaruh foreign debt, exchange rate, growth opportunity, firm size, liquidity, dan profitability terhadap hedging decision pada perusahaan sektor energi di BEI periode 2019-2023 - Hardiyanti, Andhini Agustine; Hartono, Ulil (Jurnal Ilmu Manajemen, 2025)
Participation in international transactions inherently exposes companies to risks, particularly those arising from exchange rate fluctuations. Therefore, it is essential for companies to manage these risks through preventive measures such as hedging, which serves as a strategic tool to mitigate and minimize potential financial losses. This study aims to determine the effect of foreign debt, exchange rate, growth opportunity, firm size, liquidity, and profitability on hedging decisions in energy sector companies listed on the IDX from 2019 to 2023. The population of this study consists of 90 energy sector companies listed on the IDX. The sample used comprises 39 companies, selected through purposive sampling techniques. The data is processed using IBM SPSS 25 with logistic regression analysis technique. The results of this study indicate that foreign debt and firm size positively affect hedging decisions, while liquidity negatively affects hedging decisions. Whereas, exchange rate, growth opportunity, and profitability show no significant effect on hedging decisions. Given these findings, energy sector companies are advised to prioritize factors that significantly influence hedging decisions, particularly foreign debt, firm size, and liquidity. By incorporating these considerations into their financial strategies, companies can improve decision-making accuracy, safeguard cash flow, and enhance financial stability.